A Fully Flexible Potential Model for Carbon Dioxide - 朱爱梅 张新波 刘庆林 张秋根 (Chinese journal of chemical engineering, 2009)
A fully flexible potential model for carbon dioxide has been developed to predict the vapor-liquid coexistence properties using the NVT-Gibbs ensemble Monte Carlo technique （GEMC）. The average absolute deviation between our simulation and the literature experimental data for saturated liquid and vapor densities is 0.3% and 2.0%, respectively. Compared with the experimental data, our calculated results of critical properties （7.39 MPa, 304.04 K, and 0.4679 g·cm^-3） are acceptable and are better than those from the rescaling the potential parameters of elementary physical model （EPM2）. The agreement of our simulated densities of supercritical carbon dioxide with the experimental data is acceptable in a wide range of pressure and temperature. The radial distribution function estimated at the supercritical conditions suggests that the carbon dioxide is a nonlinear molecule with the C=O bond length of 0.117 nm and the O=C=O bond angle of 176.4°, which are consistent with Car-Parrinello molecular- dynamics （CPMD）, whereas the EPM2 model shows large deviation at supercritical state. The predicted self-diffusion coefficients are in agreement with the experiments.